2019
DOI: 10.1002/msc.1380
|View full text |Cite
|
Sign up to set email alerts
|

Obesity, depression and hip pain

Abstract: Introduction: Up to 64% of the general population reports experiencing chronic pain,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 33 publications
2
24
0
Order By: Relevance
“… 27 Moreover, a cross-sectional study of 2515 adult participants has suggested that elevated depression scores were significantly and independently associated with disabling chronic hip pain. 29 Although genetic factors are likely to contribute to pain at different sites, our negative findings suggest that nongenetic triggers may be more relevant in the co-occurrence of facial, knee, or hip pain with depression. However, although our results suggest a strong evidence of null association of depression with facial, hip, and knee pain (ORs virtually equal to 1), we had limited power for these 3 pain traits due to small sample sizes.…”
Section: Discussionmentioning
confidence: 71%
“… 27 Moreover, a cross-sectional study of 2515 adult participants has suggested that elevated depression scores were significantly and independently associated with disabling chronic hip pain. 29 Although genetic factors are likely to contribute to pain at different sites, our negative findings suggest that nongenetic triggers may be more relevant in the co-occurrence of facial, knee, or hip pain with depression. However, although our results suggest a strong evidence of null association of depression with facial, hip, and knee pain (ORs virtually equal to 1), we had limited power for these 3 pain traits due to small sample sizes.…”
Section: Discussionmentioning
confidence: 71%
“…A total of 6,049 studies were excluded based on the screening of titles and abstracts, leaving 193 studies for full text analysis. A further 74 studies were excluded as they did not meet the review’s inclusion criteria: 37 studies only included BMI as their measure of obesity [ 17 51 ], 18 studies did not examine any associations between fat mass and pain [ 50 , 52 67 ], nine studies examined adiposity within a specific muscle [ 68 – 75 ], five studies did not specify a site of pain [ 76 79 ], two studies only examined multisite pain [ 80 , 81 ], and three studies examined pain in children [ 82 – 84 ].…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, since possible causes of hip osteoarthritis pain may be largely behavioral, a carefully organized set of behavioral based interventions, may predictably assist in efforts to reduce, reverse, or minimize the extent of hip osteoarthritis pain and suffering in many cases without excessive reliance on surgery, as proposed by Ren et al [52], as well as in those undergoing surgery [87]. In particular, to avert the likelihood of any ensuing peripheral and central sensitization and neuropathic pain syndromes as is being observed in this progressive disease quite frequently in recent research studies, the clinician or primary caregiver should spare no efforts in collaborating with the patient to apprise them of injurious behaviors that can exacerbate their pain.…”
Section: Discussionmentioning
confidence: 99%